La incidencia del liderazgo del rector en el desarrollo académico – administrativo del Instituto Técnico Superior “Soberanía Nacional” del cantón Paquisha, provincia de Zamora Chinchipe. Período: 2008-2009. Lineamientos alternativos - Viñán Torres, Martha Elena (2012)
The present investigation work, has as main axis the to know and to demonstrate the grade of incidence of the rector's leadership, in the academic and administrative development in the Institute Superior Technical National" "Sovereignty of the canton Paquisha, county of Zamora Chinchipe. This purpose was achieved on the base of the theoretical elements developed during the formation process; the position of the hypotheses, and its operability reflected in the variables, indicators and indexes; and, the prosecution of the information received for: the authorities, educational, students, personal of support administrative family y padres, applying surveys, test, and you interview those involved of the educational community. The Academic-administrative limited Development of the Institute Superior Technical National "Sovereignty of the Canton Paquisha, County of Zamora Chinchipe in the period 2008 -2009. He/she is due to the Rector's scarce leadership; based by an appreciable majority of the educational community that expresses not to have: the trust, motivation and collaboration of the authority; their to work is qualified as an administrator, with weak leadership. The absence of the leadership, excludes to the Institute of the academic innovation, of a qualification plan, and of the coordination of a development plan that requires of the work in team in the modern administration, to face the competition of an education of quality. The investigation group, in front of the necessity of generating spaces actitudinales and of reflection, around the academic-administrative development, it outlines a qualification event in Leadership, understanding each other as qualification event, to a process by means of which is possible to upgrade, and to innovate the personnel in thematic of great importance that are good to develop the work and to improve the yield in the same one, therefore the topics have more than enough leadership, work of quality, efficiency and effectiveness they are the guidelines to base them and to execute them in this qualification, directed the educational and administrative personnel of the Institute Superior Technical National" "Sovereignty of the canton Paquisha.